2019
DOI: 10.1177/2515841419869761
|View full text |Cite
|
Sign up to set email alerts
|

Primary glaucoma surgery in Fuchs’ heterochromic uveitis: a comparison of trabeculectomy versus deep sclerectomy

Abstract: Background: Deep sclerectomy offers the potential advantage of less postoperative inflammation and better survival in Fuchs’ patients. The aim of this study was to compare survival and safety profiles of Fuchs’ heterochromic uveitis patients undergoing trabeculectomy or deep sclerectomy. Methods: A retrospective study was conducted of two separate cohorts who had undergone either trabeculectomy or deep sclerectomy. Patient demographics, best-corrected visual acuity, intraocular pressure, antimetabolite used, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Several articles have shown that deep sclerectomies have a high success rate with improved outcomes when combined with intraoperative MMC [42–44,45 ▪ ]. Modified combined CO 2 laser-assisted deep scleral sclerectomy (CLASS) is a new form of deep sclerectomy and has shown to be effective in treating uveitic glaucoma patients.…”
Section: Other Surgical Optionsmentioning
confidence: 99%
“…Several articles have shown that deep sclerectomies have a high success rate with improved outcomes when combined with intraoperative MMC [42–44,45 ▪ ]. Modified combined CO 2 laser-assisted deep scleral sclerectomy (CLASS) is a new form of deep sclerectomy and has shown to be effective in treating uveitic glaucoma patients.…”
Section: Other Surgical Optionsmentioning
confidence: 99%